2012
DOI: 10.4314/ajtcam.v9i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Therapeutic Effect of Transcatheter Arterial Chemoembolization Combined with Compound Kushen Injection in Hepatocellular Carcinoma

Abstract: Compound Kushen Injection (CKI) is Sophora flavescens and Heterosmilacis japonicae extract. Meta-analysis confirmed that CKI plus transcatheter arterial chemoembolization (TACE) is more superior to TACE alone for unresectable hepatocellular carcinoma (UHCC) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…While the potent effects of FKI in clinical settings are beginning to undergo quantitative statistical analysis [47], the quality and reproducibility of FKI preparations remains in question. These are common concerns with many traditional Chinese medicinals.…”
Section: Discussionmentioning
confidence: 99%
“…While the potent effects of FKI in clinical settings are beginning to undergo quantitative statistical analysis [47], the quality and reproducibility of FKI preparations remains in question. These are common concerns with many traditional Chinese medicinals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun et al observed that CKI plus transcatheter arterial chemoembolization (TACE) is superior to TACE alone. They suggested that CKI could be a complementary drug with TACE to inhibit the growth of hepatocellular carcinoma, suppress tumor metastasis, reduce the incidence of pain and improve the quality of life in patients with unresectable hepatocellular carcinoma [31] . Bao et al have conducted a systematic literature research, which revealed a positive effect of CKI on bone cancer pain: compared with radiotherapy or bisphosphonates, CKI showed significant effects on the improvement of pain relief in patients with bone cancer pain and the increase in Karnofsky scores (KPS).…”
Section: Studies On Compound Kushen Injectionmentioning
confidence: 99%
“…Six meta-analyses compared the outcomes of TACE in combination with TCMs versus TACE alone [1819, 79, 81, 108, 122]. Three of them favored the combination therapy in term of OS [18, 79, 108]; one favored the combination therapy in terms of 1-, 2-, and 3-year survival, but not 6-month survival [19]; one favored the combination therapy in term of 2-year survival, but not 1-year survival [122]; one did not report the survival data [81].…”
Section: Tacementioning
confidence: 99%
“…Four of them favored the combination therapy in term of quality of life [1819, 79, 108]. Another two did not report the relevant data [81, 122].…”
Section: Tacementioning
confidence: 99%